Non-covalent Interaction With SUMO Enhances the Activity of Human Cytomegalovirus Protein IE1 - Tripathi, Vasvi; Chatterjee, Kiran Sankar; Das, Ranabir (Frontiers in Cell and Developmental Biology, 2021)
Viruses interact with the host SUMO pathway to optimize the host cell for replication. The Human Cytomegalovirus (HCMV) Immediate-Early protein 1 (IE1) is the first viral protein to express during infection. It is a multifunctional and conditionally essential protein for HCMV infection. SUMO regulates several cellular processes that are also targets of IE1. Consequently, IE1 exploits SUMO to regulate these processes. However, details of the non-covalent interaction between SUMO and IE1 are unknown. We report two SUMO-Interacting Motifs (SIMs) in IE1, one at the end of the N-terminal core domain and another in the C-terminal domain. NMR titrations showed that IE1-SIMs bind to SUMO1, but not SUMO2. Two critical functions of IE1 are deSUMOylation of Promyelocytic leukemia protein (PML) and transactivation of viral promoters. Although IE1-SIMs are not involved in PML deSUMOylation, they are critical for the transactivation activity. The transactivation activity of IE1 was considered to be merely a consequence of its PML deSUMOylation activity. Our results uncover the non-covalent interactions between IE1 and SUMO, and suggest that transactivation and PML deSUMOylation are independent activities of IE1.